2018
DOI: 10.1007/s40259-018-0280-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of the Interleukin-4/Interleukin-13 Signaling Pathway: In Allergy and Beyond

Abstract: Inflammation triggered by interleukin-4 (IL-4)/IL-13 is mediated by IL-4 and IL-13 receptors that are present on multiple cell types, including epithelial cells, smooth muscle, fibroblasts endothelial cells and immune cells. IL-4 exerts its activities by interacting with two specific cell surface receptors: one designated the type 1 IL-4 receptor (IL-4R); the other designated the type 2 IL-4R, a receptor complex that is also the functional receptor for IL-13. "Traditionally," IL-4 and IL-13 have been studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 130 publications
1
40
0
1
Order By: Relevance
“…In our study, a significant increase in IL-13 was observed in the OVA-challenged animals compared to nonchallenged animals. Tissue damage was also caused by increased IL production, which is highly involved in the asthma inflammatory process 43 . IL-13 is related to airway hyperresponsiveness 44 , which was not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a significant increase in IL-13 was observed in the OVA-challenged animals compared to nonchallenged animals. Tissue damage was also caused by increased IL production, which is highly involved in the asthma inflammatory process 43 . IL-13 is related to airway hyperresponsiveness 44 , which was not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out the importance of IL-4, IL-13, and their receptors in allergic diseases, with an emphasis on asthma, atopic dermatitis, and EoE ( 156 ). Therefore, the following agents are being investigated.…”
Section: Natural History and Prognosismentioning
confidence: 99%
“…3.2 Lebrikizumab and tralokinumab: anti-IL-13 mAb IL-13, a major type 2 cytokine secreted from T lymphocytes, is highly elevated in AD both in blood and in skin [68]. Additionally, IL-13 is considered to be a key cytokine of type 2 inflammation with a number of effects on a variety of cells, excluding T lymphocytes [69]. Two antibodies against IL-13 have been studied in AD so far.…”
Section: Dupilumab: Anti-il-4ra Mabmentioning
confidence: 99%